Antecedents of job embeddedness and its effect on proactive customer service performance of frontline employees in the hospitality industry - Chan, Wei Leong (2018)
The highly competitive hospitality business environment and the ever rising customer expectations have urged scholars and managers to pay constant attention to employees’ customer service performance. On top of in-role behaviours, employees are expected to proactively demonstrate extra-role behaviours to enhance customer experience. However, what galvanizes such proactive extra-role service behaviours, theoretically termed as proactive customer service performance, remains an underexplored issue. Anchoring in the hospitality, customer service performance, and human resource management literature, this study captured job embeddedness as a likely antecedent. In addition, given the utility of job embeddedness, several other research gaps pertaining to its antecedents and mediating roles, as well as the relationship between off-the-job and on-the-job embeddedness, were also examined. Using self-administered questionnaires, 163 paired responses were gathered from frontline employees and their supervisors/managers in 16 hotels/resorts with a rating of four stars and five stars in Malaysia. Partial Least Square Structural Equation Modeling (PLS-SEM) analyses supported six out of the 15 hypotheses. In particular, on-the-job embeddedness had a positive relationship with proactive customer service performance but off-the-job embeddedness had no relationship with it. The associations of level of control over work hours and felt obligation with on-the-job embeddedness were marginally and significantly positive, respectively. The association between perceived organizational work-life support and on-the-job embeddedness, however, was null. Against the hypotheses, none of the proposed antecedents predicted off-the-job embeddedness and the mediating roles of off-the-job and on-the-job embeddedness were all insignificant except for the relationship between felt obligation and proactive customer service performance which was mediated by on-the-job embeddedness. As expected, off-the-job and on-the-job embeddedness correlated positively, level of control over work hours influenced perceived organizational work-life support positively, and perceived organizational work-life support affected felt obligation positively. Taken together the findings, a meaningful social exchange process from level of control over work hours to proactive customer service performance was evident. The study concluded that employees’ proactive customer service performance was contingent upon their level of control over work hours, and their job embeddedness played a sizable social exchange role in between. On-the-job embeddedness was more proximate to proactive customer service performance than was off-the-job embeddedness.